An educational tool for the genetic algorithm-based fuzzy logic controller of a permanent magnet synchronous motor drive. Issue 3 (1st July 2014) - Öztürk, Nihat; Çelik, Emre
Abstract In this study, a novel educational tool is introduced for the genetic algorithm (GA)-based fuzzy logic controller (FLC) of a permanent magnet synchronous motor (PMSM) drive. This tool provides the operating principle of PMSM, essentials of GAs, and effects of FLC parameters on the performance of GA-based FLC. The proposed educational tool regarding GA-based FLC is a unique one in its field in the literature, as such a computer-based study aiming to teach the corresponding intelligent system has not been studied before, though both GA and FLC are well-known powerful techniques. The graphical interface, developed in Microsoft Visual C#.NET platform, has a flexible and functional structure. By changing motor operating conditions as well as GA and controller parameters, useful practices can be done on the whole system under various situations without wasting time. An evaluation of the tool is given based on student feedback.